Miniature Monuments : Modeling German History. - Puff, Helmut (Media and Cultural Memory / Medien und kulturelle Erinnerung., 2014)
This study takes a material object as its starting point: small-scale models of bombed out cities. Created between 1946 and the present, these plastic renderings of places provide eerie glimpses of destruction and devastation resulting of war. This study considers these "miniature monuments" in a deep cultural history that interlaces the 16th, 18th, and 20th centuries. Miniature Monuments thus tackles a haunting paradox: building ruins.- Resumé vydavatel